Ribosome protection by ABC‐F proteins — molecular mechanism and potential drug design - Ero, Rya (2019)
Members of the ATP‐binding cassette F (ABC‐F) proteins confer resistance to several classes of clinically important antibiotics through ribosome protection. Recent structures of two ABC‐F proteins, Pseudomonas aeruginosa MsrE and Bacillus subtilis VmlR bound to ribosome have shed light onto the ribosome protection mechanism whereby drug resistance is mediated by the antibiotic resistance domain (ARD) connecting the two ATP binding domains. ARD of the E site bound MsrE and VmlR extends toward the drug binding region within the peptidyl transferase center (PTC) and leads to conformational changes in the P site tRNA acceptor stem, the PTC, and the drug binding site causing the release of corresponding drugs. The structural similarities and differences of the MsrE and VmlR structures likely highlight an universal ribosome protection mechanism employed by antibiotic resistance (ARE) ABC‐F proteins. The variable ARD domains enable this family of proteins to adapt the protection mechanism for several classes of ribosome‐targeting drugs. ARE ABC‐F genes have been found in numerous pathogen genomes and multi‐drug resistance conferring plasmids. Collectively they mediate resistance to a broader range of antimicrobial agents than any other group of resistance proteins and play a major role in clinically significant drug resistance in pathogenic bacteria. Here, we review the recent structural and biochemical findings on these emerging resistance proteins, offering an update of the molecular basis and implications for overcoming ABC‐F conferred drug resistance.